Leveraging Pension Fund Investment for Domestic Development : Namibia’s Regulation 29 Approach - World Bank (World Bank, Washington, DC, 2020)
The note describes Namibia’s approach to support domestic economic development via mandating investment of a percentage of the large pool of local institutional capital in alternative financing vehicles within the context of an underdeveloped capital market. Namibian approach diverges from international practice. Namibia Financial Institutions Supervisory Authority (NAMFISA) – the national regulator - instituted mandatory requirements that all pension (and insurance) funds invest in unlisted Namibian companies, formalized the unlisted investment market, created specialized intermediaries and introduced high level of regulatory oversight for both investment managers and investment vehicles. The note describes the investment vehicles and regulatory structure established by NAMFISA, experience of market participants and perspective of the nascent asset management industry managing unlisted investments. The note also summarizes lessons learnt and considers whether such structures could be applied in countries with similar market and economic contexts.